(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت هذه الدراسة إلى التعرف على أهمية استخدام الإجراءات التحليلية في عملية تدقيق الحسابات باكتشاف مخاطر التدقيق وتوجيه انتباه المدقق للأخطاء المحتملة، وإظهار دور الإجراءات التحليلية في خفض تكلفة عملية التدقيق، ومن ثم تحسين إنجاز عملية التدقيق. ولتحقيق أهداف الدراسة تم التعرف في الجانب النظري للبحث على المفهوم والأهمية والأساليب للإجراءات التحليلية، أما الجانب الميداني للبحث شمل عينة من مدققي الحسابات العاملين في الجمهورية العربية السورية، وبلغ العدد في العينة النهائية والمعتمدة لأغراض البحث والتحليل (60) مدققاً مزاولاً. وانتهت الدراسة إلى أهمية استخدام الإجراءات التحليلية لتخفيض مخاطر التدقيق المحتملة، إضافة إلى دورها الفعال في تخفيض تكلفة عملية التدقيق. This study aimed to identify the importance of the use of analytical procedures in the audit process through the discovery of the audit and the auditor to draw the attention of potential risk of errors, and to show the role of analytical procedures in reducing the cost of the audit process, thus improving the completion of the audit process. To achieve the objectives of the study have been identified in the theoretical side of the search on the concept and importance and methods of analytical procedures, and the field side to find a sample of auditors working in the Syrian Arab Republic accounts included, the number of the final sample and approved for the purposes of research and analysis (60) auditor factor. The study concluded the importance of using analytical procedures to reduce the potential risk of audit, as well as effective role in reducing the cost of the audit process.